Writing feminism : South Asian voices - Chakravarty, Radha; Hosena, Selinā, 1947- (Dhaka : University Press Limited, 2010)
Collection of short storeis reflecting social conditions of women in South Asia, written in English and translated into English from various South Asian languages.
Keywords: Short stories, South Asian -- Translations into English; South Asian fiction -- 20th century -- Translations into English; South Asian fiction -- 21st century -- Translations into English; South Asian fiction (English) -- 20th century; South Asian fiction (English) -- 21st century; Women -- South Asia -- Fiction